Human dignity in the Judaeo-Christian tradition: Catholic, Orthodox, Anglican and Protestant perspectives - Loughlin, John (Bloomsbury Academic, 2019)
"Dignity is a fundamental aspect of our lives, yet one we rarely pause to consider; our understandings of dignity, on individual, collective and philosophical perspectives, shape how we think, act and relate to others. This book offers an historical survey of how dignity has been understood and explores the concept in the Judaeo-Christian tradition. World-renowned contributors examine the roots of human dignity in classical Greece and Rome and the Scriptures, as well as in the work of theologians, such as St Thomas Aquinas and St John Paul II. Further chapters consider dignity within Renaissance art and sacred music. The volume shows that dignity is also a contemporary issue by analysing situations where the traditional understanding has been challenged by philosophical and policy developments. To this end, further essays look at the role of dignity in discussions about transhumanism, religious freedom, robotics and medicine. Grounded in the principal Christian traditions of Catholicism, Orthodoxy, Anglicanism, and Protestantism, this book offers an interdisciplinary and cross-period approach to a timely topic. It validates the notion of human dignity and offers an introduction to the field, while also challenging it."--Bloomsbury publishing